Predictors in ASD: The Importance of Parents' Perception - Mira Coelho, Alda; da Conceição, Virgínia (Frontiers in Psychiatry, 2021)
Abstract It is important to understand what may predict different developmental trajectories of children with Autism Spectrum Disorder (ASD) and parent’s concerns may be an important contribute. We examined clinical features of 55 children with ASD, in two moments of evaluation, in order to understand this process. They were assessed with Autism Diagnostic Observation Schedule (Autism Diagnostic Observation Schedule) at both moments. We selected two groups, based on the results of ADOS at moment 2. We also selected questions from a questionnaire to parents in order to know if early parent’s concerns can predict ASD prognosis because we believe in the importance of parent’s involvement in the treatment process from the beginning. We found a significant correlation between some subscales of ADOS with the better evolution of children and with the results of parent’s questionnaire.